Budaya Kesantunan Penggunaan Kata: Maaf, Tolong, Terima Kasih dalam Berkomunikasi - Ary Setyadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
The existence of the words: please, sorry, thank you are able to create their own cultural behavior in the implementation of events/meetings/celebrations; so that the three words can be used by anyone, by the general public or by officials. Assessment efforts, especially those with oral data on the implementation of speeches, have not received special attention. The theory used is based on the application of sociolinguistic theory and pragmatic theory. The implementation of the implementation method is based on three strategic stages: 1. data provision, 2. data classification and analysis, and 3. writing preparation. The data departs from oral and written sources, the existence of the two data sources is complementary. The application of the data supply method starts with "listening" with the "reading" technique followed by carding the data, and classifying the data based on the context of the speech. The objectives to be achieved are related to: 1. a description of the use of each word separately, and 2. a description of the combining power between the two/three. The final results of the assessment show that: the use of the words please, sorry, thank you is able to create cultural behavioral characteristics when speaking in communication. The existence and/or use of these three words gives color to the creation of a harmonious relationship between the speaker/communicator/O1 and the listener/communicant/O2.